Risk factors associated with sport-related injuries in para athletes: an analysis of the 2012 and 2016 Summer Paralympic Games - Adam, Faatima (Stellenbosch : Stellenbosch University, 2022)
Thesis (M Sport Sc )--Stellenbosch University, 2022.